2007
DOI: 10.1016/j.resp.2006.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 enhances the sensitizing effect of hyperthermia on pulmonary C-fibers in rats

Abstract: This study was carried out to investigate whether the pulmonary C-fiber hypersensitivity induced by hyperthermia is altered by prostaglandin E 2 (PGE 2 ). Single-unit afferent activities of pulmonary C-fibers were recorded in anesthetized, artificially ventilated rats when the intrathoracic temperature (T it ) was maintained at normal (N; ~36°C) and hyperthermia levels (H; ~41°C) by perfusion of heated saline into the thoracic chamber for 3 min. After ~20 min of recovery, the fiber activities were recorded aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Indeed, Kubista et al showed that cangrelor antagonises the inhibition of neuronal Ca 2+ channels by adenine nucleotides, which is mediated by P2Y 12 and paralleled by inhibition of cAMP accumulation (23). The importance of cAMP in the activation of afferent C-fibers is highlighted by the effect of prostaglandin E 2 (PGE 2 ), which potentiated hyperthermia-induced hypersensitivity of vagal pulmonary C-fibers through its interaction with Gs-coupled EP2 and EP4 receptors (24). Moreover, inhalation of PGE 2 aerosol significantly increased the dyspnoic sensation during exercise in healthy human subjects, without inducing changes in airway resistance or lung volume (25).…”
Section: Hypothesis: Ticagrelor-induced Dyspnea Is Mediated By Inhibimentioning
confidence: 99%
“…Indeed, Kubista et al showed that cangrelor antagonises the inhibition of neuronal Ca 2+ channels by adenine nucleotides, which is mediated by P2Y 12 and paralleled by inhibition of cAMP accumulation (23). The importance of cAMP in the activation of afferent C-fibers is highlighted by the effect of prostaglandin E 2 (PGE 2 ), which potentiated hyperthermia-induced hypersensitivity of vagal pulmonary C-fibers through its interaction with Gs-coupled EP2 and EP4 receptors (24). Moreover, inhalation of PGE 2 aerosol significantly increased the dyspnoic sensation during exercise in healthy human subjects, without inducing changes in airway resistance or lung volume (25).…”
Section: Hypothesis: Ticagrelor-induced Dyspnea Is Mediated By Inhibimentioning
confidence: 99%
“…For example, a classical pro-nociceptive mediator prostaglandin E 2 sensitizes the vagal C-fiber terminals to physical and chemical stimuli via direct action on the EP2 receptor in their neuronal membrane (Ho et al, 2000; Lee et al, 1995; Zhang et al, 2007). Mechanistically, the PGE 2 –induced sensitization has been attributed to the combination of receptor-specific sensitization (such as TRPV1 sensitization) and an increase in non-specific sensory excitability (Kwong et al, 2002).…”
Section: Putative Vagal Nociceptive Nerve Fibers In the Lungsmentioning
confidence: 99%
“…This surgery results in total subdiaphragmatic vagal denervation, including hepatic afferent vagal denervation, but it does not eliminate supradiaphragmatic (e.g., pulmonary) innervation. Together with the liver, the lungs are the major sources of peripheral PGE 2 synthesis during fever (25,82), and PGE 2 has been shown to affect pulmonary vagal afferents in a receptor-specific manner (95). To eliminate the possibility that supradiaphragmatic vagus could convey febrigenic signals to the brain, we performed experiments with bilateral cervical vagotomy.…”
Section: Intravenous Pge 2 -Induced Fever Can Occur Independently Of mentioning
confidence: 99%